Pengaruh Pelapisan Virgin Coconut Oil (VCO) terhadap Kualitas Internal Telur Ayam Ras selama Penyimpanan Suhu Ruang - Nur, Nur Eni; Jumriani, Jumriani (Fakultas Peternakan Universitas Madako Tolitoli, 2025)
Chicken eggs are a highly nutritious food, but they are prone to quality deterioration during storage due to physical and chemical changes. One effort to extend their shelf life is by using natural coating materials such as Virgin Coconut Oil (VCO). This study aimed to evaluate the effect of VCO coating on the internal quality of chicken eggs during storage at room temperature. The experiment was conducted using a Completely Randomized Design (CRD) with seven treatments and four replications, resulting in 28 experimental units. The treatments consisted of fresh eggs (control), uncoated eggs stored for 7, 14, and 21 days, and VCO-coated eggs stored for the same periods. The observed variables included Haugh Unit, egg weight, air cell size, albumen index, and yolk index. Data were analyzed using analysis of variance (ANOVA), and significant differences among treatments were further tested with Duncan’s Multiple Range Test (DMRT) at the 5% significance level. The results showed that VCO coating significantly preserved the internal quality of eggs compared to uncoated eggs. Eggs treated with VCO had higher Haugh Unit values, albumen and yolk indices, and experienced lower weight loss and air cell enlargement during storage. It can be concluded that coating eggs with VCO is a simple and effective method to maintain the quality of chicken eggs during storage at room temperature.